Bronchocentric Granulomatosis: Clinical Course Illustrated by Serial Computerized Tomography of the Chest. Issue 4 (1994) - Granton, John T; Chamberlain, Dean W; Hyland, Robert H
Abstract : Bronchocentric granulomatosis is a pathological process characterized by granulomatous inflammation in conducting airways. A case of bronchoccntric granulomatosis of unknown etiology in a previously well 24-year-old female is reported. The variable and often rluctuating course of this entity and its response to corticosteroids is demonstrated by serial computerized tomography nr the chest. The pathology, etiology and therapy ofbronchoccntric granulomatosis is reviewed.